EVALUATION OF THE ANTIDIABETIC EFFECTS OF THE HYDROETHANOLIC EXTRACT OF THE TRUNK BARK OF LANNEA ACIDA A. RICH. (ANACARDIACEAE) ON FRUCTOSE-INDUCED DIABETIC WISTAR RATS - ABDELAZIZ KOUSSOUBÉ; FILKPIÈRÈ LÉONARD DA; MAYA DOUKOURÉ; BASILE TINDANO; BALÉ BAYALA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Given the increasing consumption of sweet products and the preference for these products. Metabolic disorders such as diabetes appear early in life. This study aimed to evaluate the effect of hydroethanolic extract of Lannea acida (L. acida) trunk bark (HEELA) on the impact of daily fructose consumption on the onset of type 2 diabetes. Methods: Four groups of male Wistar rats were fed a 10% fructose-rich drinking water for ten weeks to induce diabetes. At the beginning of the 11th week, the three groups were treated with 40. 100 and 200 mg/kg body weight (bw) HEELA for six weeks. The negative control group continued to receive fructose without treatment. The fifth group was fed fructose-free drinking water (neutral control). Blood sugar levels were measured every two weeks, and biochemical parameters such as lipids and transaminases were assessed. The area under the curve was determined. Histopathological sections of the pancreas and liver were also carried out. Results: The results showed a significant (p<0.001) decrease in high-fructose diet-induced increases in blood glucose, relative liver and pancreas weights, area under the curve, triglyceride, ASAT, and ALAT concentrations following HEELA administration at 200 mg/kg body weight. Conversely, a significant increase (p<0.001) in the fructose-induced decrease in HDLc. The effects of fructose on liver and pancreas structure were corrected by HEELA. Conclusion: HEELA improves the blood glucose, lipid profiles and supports liver and pancreas functions. In addition, it protects against the hepatic and pancreatic tissue damage mediated by the daily fructose consumption.